Study on Cross-cultural Conflict Management in Sino-foreign Joint Ventures in China - WU, Yiming (Advances in Social Sciences Research Journal, 2014)
Ever since the mid-1990s, with the rapid development of economic globalization and information, a new wave of transnational business operations has been engulfing the world .However, the operation of cross-board business is never as smooth as people think it might be. The common challenges that confront transnational companies stem from cultural difference, conflicts and unfamiliar cultural environment, pushing the science of transnational management into a new phase-Cross-cultural Management. In an era when China’s economy has been burgeoning and its interaction with the rest of the international community has been on an unprecedented scale, cross-cultural management has become an inevitable and inescapable issue facing managers of Sino-foreign joint ventures. This paper aims at analyzing the plights such as cultural difference, cultural conflicts and cross-culture management patterns that confront Sino-foreign joint ventures, in the hope of providing some suggestions and implications for Sino-foreign joint ventures, particularly Sino-U.S joint venture operating in China and Chinese companies involved in international operations.